Industry Development of Derivative Functionalized Gold Nanomaterials and Their Application in Chemiluminescence Bioanalysis: Based on the Industrial Practice of China's Central Yunnan Urban Agglomeration - Tengfei Ma; Hao Wu (Journal of Chemistry)
Electrochemiluminescence biosensor is an analytical method combining electrochemiluminescence technology with biosensor. Using nanomaterials as electrochemical luminescence sensor platform can not only immobilize a large number of biomolecules but also improve the performance of the sensor to realize the supersensitive detection of biomacromolecules. Although these methods have high sensitivity for bioanalysis, there are still some shortcomings which limit the practical application. Therefore, this paper discusses the development of functional gold nanomaterials industry and its application in chemiluminescence bioanalysis. In this paper, two methods of synthesizing luminescent functional gold nanomaterials at room temperature were studied by using chemiluminescent reagents as reducing agent and protective agent. Based on luminescent functionalized gold nanoparticles, immunoassay and DNA bioanalysis probes were constructed, and their applications in chemiluminescence and electrochemiluminescence bioanalysis were discussed. Finally, the simulation results show that the relative deviation between the experimental results and the existing clinical methods is less than 17%. The sensor has good stability and selectivity and can be used for the determination of CEA in human serum. The gold nanomaterials synthesized by further research have excellent chemiluminescence activity and can be used to label biomolecules and prepare biological probes. This article aims to explore the application of chemical methods in the transformation of new industries, to achieve breakthroughs in new products in industrial innovation, and to achieve the cross-fusion of management science and engineering disciplines and chemical disciplines. The industrial development of derivative functionalized gold nanomaterials has broad application prospects in biological analysis.